2022
DOI: 10.14569/ijacsa.2022.01312121
|View full text |Cite
|
Sign up to set email alerts
|

Digital Intelligent Management Platform for High-Rise Building Construction Based on BIM Technology

Abstract: In this study, the digital intelligent management platform of high-rise building construction based on BIM technology is used for real-time monitoring and management of construction progress and quality. In the data acquisition and processing layer, construction site data is obtained through RFID technology. After processing such as cleaning and integration, it is input to the BIM model layer to dynamically generate various real-time BIM models, and these real-time BIM model information is input to the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Consequently, Ying [25] confirmed in his study of: Construction of intelligent multi-construction management platform for bridges based on BIM technology, that in buildings, energy efficiency can be achieved by using insulation materials, improved architectural techniques and modified construction methodology. At the same time, Taşçı [24] confirmed that for new buildings, there are generally known passive design parameters that need to be taken into account, such as site selection, location, building orientation, environment, building form, optical and thermo-physical characteristics of the building envelope, solar control and natural ventilation systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, Ying [25] confirmed in his study of: Construction of intelligent multi-construction management platform for bridges based on BIM technology, that in buildings, energy efficiency can be achieved by using insulation materials, improved architectural techniques and modified construction methodology. At the same time, Taşçı [24] confirmed that for new buildings, there are generally known passive design parameters that need to be taken into account, such as site selection, location, building orientation, environment, building form, optical and thermo-physical characteristics of the building envelope, solar control and natural ventilation systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the digital era, great and increasing attention has been devoted to research on automated methods for real-time monitoring of activities in construction sites [15,24,25]. These modern approaches are able to offer better performance with respect to the most traditional techniques, which are typically based on manual collection of on-site work data and human-based construction project monitoring.…”
Section: Related Workmentioning
confidence: 99%
“…The world is currently at the dawn of a new era characterized by a global transformation reshaping how we interact with our surroundings and each other. This global transformation is being fueled by rapid advancements in intelligent technologies [1,2], such as artificial intelligence (AI), big data, and the Internet of Things (IoT) [3,4]. These intelligent technologies increasingly connect people and their surrounding environments in previously unimaginable ways.…”
mentioning
confidence: 99%